Learning Organization: Profile and Influence on Leadership Attitudes of Members of the Chemistry Education Department Student Association - Evi Sapinatul Bahriah; Andi Anugrah; Irnin Agustina Dwi Astuti; Mochammad Sukardjo; Muhammad Japar (AL-ISHLAH: Jurnal Pendidikan, 2023)
Student organizations as learning organizations are a place for students to learn and develop themselves to broaden their horizons and increase knowledge, and students' personal integrity. The Chemistry Education Department Student Association   is a learning organization that can improve leadership attitudes and character. However, only a few students want to be involved in this organization. Therefore, the purpose of this study was to find out the profile of learning organization in internal campus student organizations, especially the   Chemistry Education and its influence on student leadership attitudes. The research method used is survey method. This research was conducted from 15 September to 10 November 2022 at the Department of Chemistry Education. The sample of this research was 50 students who were members of the   Chemistry Education. The data collection technique uses an online questionnaire instrument (google form). The data obtained were analyzed by descriptive quantitative. Based on the research data it can be concluded that: 1) the profile of learning organization in internal campus student organizations is included in the very good category with an average score percentage of 82.9%; 2) the leadership attitude of HMPS member students is included in the good category with an average percentage score of 78.6%; and 3) there is a positive relationship between learning organization and student leadership attitudes. So it can be concluded that HMPS as a learning organization can influence student leadership attitudes.